Археолог Юліан Кулаковський: сучасна історіографія - Арасланова, С.М. (Сіверщина в історії України, 2014)
Стаття присвячена відомому науковцю
Ю.А. Кулаковському та його досягненням в сфері археології.
Розглядаються погляди та оцінки сучасних істориків щодо
постаті археолога. Визначається вклад Ю.А. Кулаковського
в розвиток історичної науки. Статья посвящена известному научному деятелю
Ю.А. Кулаковскому и его достижениям в сфере археологии.
Рассматриваются взгляды и оценки современных историков
относительно личности археолога. Определяется вклад
Ю.А. Кулаковского в развитие исторической науки. The article is devoted to the known scientist Yulian A.
Kulakovskyi and his achievements in the field of archaeology. Looks
and estimations of modern historians are examined, in relation to
the figure of archaeologist. The contribution of Yu.A. Kulakovskyi to
development of historical science is determined.